Community leadership practices in Edo State Nigeria: Justification for a Biomimetic-based alternative in community development - H. E., Adebola; Fashae G. C, Abey (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This article is the first of a two-part assessment of leadership practices in community development processes. In this first part, community leadership practices (CLPs) are established as everyday actions executed by community leaders in the administration of processes to achieve communal development. In which case, community development associations (CDAs) should be agents that facilitate community development. Therefore, the continued disbandment of CDAs by the government of Edo State Nigeria in the past 6 years is odd. Postulating that the prevailing anti-development leadership practices is the reason behind the disbandment, the authors assessed the state of CLPs in the study area to determine the justification or otherwise, for a Biomimetic leadership alternative. The assessment was by observation, news reports and document analysis. This article affirmed that dominant anti-development practices of CDA leaders are critical to lack of development and recommended drawing leadership lessons from resilient bio-communities for application in human communities